THe Analysis of Library Visitor Satisfaction Using the Servqual Method - Rini Agustina; Dodit Suprianto; Nandono Cahyo (Indonesian Journal of Engineering Research, 2020)
The purpose of this study was to determine the level of satisfaction of library services with the SERVQUAL method based on five dimensions, such as tan-gible, reliability, responsiveness, assurances, and empathy. The satisfaction evaluation of library services is needed because the number of library visitors is increasingly decreasing. This study tries to find out the things that cause the number of library visitors to decrease while knowing what services need to be improved. Based on the results of library service evaluation tests, 68% of visitors said they were not satisfied with library services, with an average value of SERVQUAL (-0.2) from 25 criteria and 105 respondents. This data shows some library services that must be repaired by schools by improving facilities and services to visitors.